Lidocaine-Epinephrine-Tetracaine Gel Is More Efficient than Eutectic Mixture of Local Anesthetics and Mepivacaine Injection for Pain Control during Skin Repair in Children: A Prospective, Propensity Score Matched Two-Center Study - Königs, Ingo; Wenskus, Julia; Boettcher, Johannes; Reinshagen, Konrad; Boettcher, Michael (European Journal of Pediatric Surgery, 2019)
Introduction Skin lacerations are common in children and their repair is a very unpleasant experience for a child. While pain management has been recognized as a key element of high-quality patient care, recent studies report that pain management in the pediatric emergency departments is still suboptimal. Lidocaine-epinephrine-tetracaine (LET) gel could potentially improve the traumatic experience caused by skin repair as it obviates the need for infiltration. Thus, the aim of the current study was to compare local eutectic mixture of local anesthetics (EMLA) plus mepivacaine infiltration with topical anesthetics (LET-gel).Materials and Methods Prospective, propensity score-matched multicenter study including all children between 3 and 16 years presented at two centers. After anesthetics (LET vs. EMLA and infiltration) standardized skin repair was performed. Pain assessment was performed using the faces pain rating scale or visual analogue scale. Follow-up, performed 2 weeks after initial presentation, assessed wound infection rates and overall satisfaction.Results Of 73 subjects 59 children (37 LET vs. 22 EMLA) were included after propensity score matching. Groups had similar baseline characteristics. Pretreatment was significantly less painful in LET versus local anesthetics group. Pain during skin repair was similar between groups (LET and EMLA with mepivacaine infiltration) and both groups demonstrated similar efficacy (procedure time, need for secondary infiltration, infection rate). Ultimately, pain levels during pretreatment and the surgical procedure were perceived significantly higher by the children than estimated by parents or surgeons.Conclusion In conclusion, it appears that LET is superior to conventional anesthesia including mepivacaine infiltration in the pediatric emergency departments. Pretreatment with LET is significantly less painful but equally effective. Hence, we recommend LET as a topical anesthetic in the pediatric emergency department.
Keywords: LET; pain management; children; skin